Letter from Carl D. Duncan to Patricia Whiting, March 7, 1966 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan compliments Whiting's mother on the upbringing of Whiting and her siblings and offers a short toast. Duncan also mentions his excitement over attending a lecture by Buckminster Fuller.